A Meta-analysis on the Security Control Measures in Cloud Migration - S.P. , Sreeja; B. , Meenakshi Sundaram (International Journal of Psychosocial Rehabilitation, 2020)
The data need to be shared on a cloud platform with high security and maintained in the cloud in a secure manner for any customer storing the information. There are various cloud providers who provide separate data centers and are present in different locations. This enables it to act as a backup for the customer, and it should be secured. This paper discusses the cloud computing security measures.